Assessing Cameroon's foreign policy through modelling and discourse analysis (1982-2002) - (:unkn) unknown (My University, 2021)
How can the foreign policy of a State like Cameroon be systematically assessed? The literature on diplomacy and on foreign policy analysis seem to agree, on the one hand, on the fact that the later belongs to the public policy analysis domain and, therefore, on the other hand, on the difficulty in assessing it. This, due to its particularity, groomed, among other things, in its great reactivity to the international situation and its temporal permanence. Thus, the question of the timing and criteria for assessing foreign policy has remained an unknown to be resolved. This work attempts to unravel the tangle of the possibility or not of a (systematic) assessment of foreign policy, based on the example of Cameroon. It then determines, in order to achieve this, in a complex approach, the criteria of assessibility, including that of starting not from a heavy and plural organization such as a ministry, department or agency, but from a monolithic and complete institutional role like that of President of the Republic, Head of State. It proceeds by exploiting a corpus of speeches archived over twenty years and by adopting the approach of graphic modeling and mapping, all in a hypothetico-inductive perspective specific to the sociology of International Relations. The results arrived at the end of the application of this new assessment model, show that Cameroon's foreign policy, apprehended from the diplomatic discourse, had: 1) a high Western geodiplomatic perspective, with strong roots in Western Europe and France; 2) a relatively average African geodiplomatic perspective, limited to Nigeria (bilateral diplomacy) and in Gabon and Ethiopia (multilateral diplomacy); 3) a weak Asian geodiplomatic perspective, limited to bilateral diplomacy and China. Moreover, over the period under review, Central and South America, SouthEast Asia, Oceania, the Middle East and North Africa remained diplomatic grey areas, and therefore areas of lesser interest to Cameroonian foreig
Keywords: African Research